PENGETAHUAN DAN TINDAKAN PERSONAL HYGIENE PEMULUNG SAMPAH DI TPA GANET TANJUNGPINANG - Dewi Puspa Rianda (Jurnal Kesehatan, 2014)
Dewi Puspa Rianda1)1)Jurusan Keperawatan Poltekkes Kemenkes Tanjungpinang Abstract: RelatedKnowledgeAndPersonalHygieneMeasuresOfGarbageInTPA GanetScavengerTanjungpinang.Scavengers work took thrift or specific bins for recycling. Viewed from the standpoint of health, the job of a scavenger has a very high risk for transmission of disease because scavengers working in an environment that is not conducive. Unhealthy behavior can be caused due to lack of knowledge about personal hygiene scavengers so many risk factors that occur in the garbage collector in place Waste Management Ganet Tanjungpinang. The research objective was to determine the relationship between knowledge and action about personal hygiene at scavengers in Garbage Disposal Ganet Tanjungpinang 2014.This research is a descriptive cross-sectional design. Location of the study conducted in The Waste Management Ganet Tanjungpinang and implemented in July 2014, with the object of research, amounting to 61 the number of scavengers. Analysis with Spearmen test (p=0,05). Knowledge and action research results of each scavenger of hair hygiene (21.67%; 35.00%) hand hygiene (16.67%; 26.67%) hygiene feet (38.33%; 30.00%) hygiene nails (30.00%; 36.67%) and the cleanliness of the skin (18.33%; 30%). The test results showed spearmen test p = 0.034 <0.05 means that there is a significant relationship between knowledge and personal hygiene measures scavengers.Based on the research results suggested to the Department of Health and Department of Health through the Health Center to provide and improve outreach to the scavenger pertaining to personal hygiene, and together with scavengers provide a complete hand washing with soap and a washcloth. Keyword: Knowledge, Action, Personal Hygiene, Scavenger. Abstract: Pengetahuan dan Tindakan Personal Hygiene Pemulung Sampah di TPA Ganet Tanjungpinang. Pemulung kerja mengambil barang bekas atau sampah khusus untuk daur ulang. Dilihat dari sudut pandang kesehatan, pekerjaan pemulung memiliki risiko yang sangat tinggi untuk penularan penyakit karena pemulung yang bekerja di lingkungan yang tidak kondusif. Perilaku sehat dapat disebabkan karena kurangnya pengetahuan tentang pemulung kebersihan pribadi begitu banyak faktor risiko yang terjadi pada sampah di tempat Pengelolaan Limbah Ganet Tanjungpinang. Tujuan penelitian ini adalah untuk mengetahui hubungan antara pengetahuan dan tindakan tentang kebersihan pribadi pada pemulung di Tempat Pembuangan Sampah Ganet Tanjungpinang 2014.Penelitian ini adalah desain deskriptif cross-sectional. Lokasi dari penelitian yang dilakukan di The Pengelolaan Limbah Ganet Tanjungpinang dan dilaksanakan pada bulan Juli 2014, dengan obyek penelitian, 61 jumlah pemulung. Analisis dengan uji Spearman (p = 0,05). Pengetahuan dan penelitian tindakan hasil dari tiap pemulung kebersihan rambut (21,67%; 35,00%) kebersihan tangan (16,67%; 26,67%) kaki kebersihan (38,33%; 30,00%) kuku kebersihan (30,00%; 36.67%) dan kebersihan kulit (18,33%; 30%). Hasil tes menunjukkan uji Spearmen p = 0.034 <0,05 berarti ada hubungan signifikan antara pengetahuan dan kebersihan pribadi tindakan pemulung.Berdasarkan hasil penelitian disarankan kepada Departemen Kesehatan dan Departemen Kesehatan melalui Puskesmas untuk memberikan dan meningkatkan jangkauan kepada pemulung yang berkaitan dengan kebersihan pribadi, dan bersama-sama dengan pemulung memberikan cuci tangan lengkap dengan sabun dan kain lap Kata kunci: Pengetahuan, Tindakan, Kebersihan pribadi, Pemulung